STRUKTUR DAN MAKNA FRASA NOMINAL DALAM BAHASA MAANYAN - Silmi Nur Alfiah; Asep Yudha Wirajaya (Kantor Bahasa Provinsi Gorontalo, 2017)
The purpose of this reserach is to describe structure and meaning of nounphrases in Maanyan language using theory of phrase structure fromBa’dulu. The data for this research are sentences in Maanyan languagecontaining noun phrases. The data were analyzed with agih method andseveral advenced techniques. The results indicate that noun phrases in BMare endocentric phrases with noun as the centre. There are eight structuresof noun phrases in BM, noun as the centre followed by (1) noun or pronounas the attribute, (2) active verb or adjective as the attribute, (3) passive verband noun as the attribute with ‘sa’ as the marker, (4) adjectiva anddemonstrative pronoun as the attribute with sa’ as the marker, (5) two ormore noun as the attribute, (6) preposisional phrase, and noun as the centrepreceded by numeral and ‘hi’ as the attribute. Noun phrase in BM haveseveral meaning, such as, summation, election, equality, explainatory,barrier, determinants, number and appellations.